(untitled) (Herald of the National Children’s Medical Center, 2025)
Cerebral palsy (CP) is a group of persistent motor function disorders caused by brain damage in early childhood. One of the most common and severe orthopedic complications in CP is spastic hip dislocation, with an incidence reaching 60% or more in patients with severe motor impairments (GMFCS IV–V). This condition leads to significant functional limitations, pain, caregiving difficulties, and reduced quality of life.